Vipera berus bites in Finlad – has anything changed during the last decade? - Taavo, Taru (My University, 2023)
The common European adder, Vipera berus, is the only indigenous venomous snake in Finland. Dozens of snakebites happen every year and most patients experience only local symptoms, but the possibility of severe complications exists. Fatal cases are very rare, and the latest fatal snakebite in Finland has been reported in the 1980’s. Patients with severe or prolonged symptoms can be treated with a specific ovine-based antivenom. The aim of this study was to obtain general information about snakebites and the use of an ovine-based antivenom. This was an epidemiological retrospective study. The material consisted of patients treated for a snakebite or a suspected snakebite in Finland at Turku University Hospital during years 2011-2019. Information about patient’s age, sex, symptoms, bite location, treatment, and duration of hospitalization, were collected. The severity of a snakebite was evaluated using the Poisoning severity score with five categories, from no symptoms to fatal. The results were compared with a previous study on the same region to determine possible changes in treatment practices and results. Vipera berus bites treated in the university hospital are common and the number of them has slowly increased during the latest decade. Severe symptoms were very rare and the number of them seems to be stable. This may be explained by public instructions to contact the health care upon a snakebite, even in the absence of symptoms. Antivenom administration is typical in the most severe cases and its use has remained at the same level. Ovine-based antivenom was mostly complication free in the study.
Keywords: Vipera berus, snakebite, antivenom, adder